Perkembangan Budaya Islam Kontemporer dan Inovasi Produksi Konten Keagamaan di Ranah Digital - Aliffiah Putri Alqohar; Bunga Aulia Maharani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of information and communication technology has transformed the dissemination of Islamic teachings, particularly through social media platforms. This study analyzes the dynamics of contemporary Islamic culture, innovations in digital religious content, and the role of digital platforms in supporting da'wah and shaping the religious identity of younger generations. The study employed a literature review by examining relevant scholarly publications on digital da'wah, social media, and Islamic education. The findings reveal that digital platforms provide broad opportunities to promote Islamic values through innovative formats such as short videos, podcasts, infographics, and animations, enabling wider public engagement. Nevertheless, the digital environment also presents challenges, including misinformation, superficial religious understanding, algorithm-driven content consumption, and the commodification of religious values. These issues highlight the need to strengthen digital literacy and integrate Islamic values into digital communication practices. The study concludes that digital platforms can serve as effective and responsible media for da'wah and Islamic religious education when supported by critical digital literacy, ethical content production, and value-based communication strategies.